2021
DOI: 10.48550/arxiv.2104.07622
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Intermediate mass dileptons as pre-equilibrium probes in heavy ion collisions

Maurice Coquet,
Xiaojian Du,
Jean-Yves Ollitrault
et al.

Abstract: The production of dileptons with an invariant mass in the range 1 GeV < M < 5 GeV provides unique insight into the approach to thermal equilibrium in ultrarelativistic nucleus-nucleus collisions. In this mass range, they are produced through the annihilation of quark-antiquark pairs in the early stages of the collision. They are sensitive to the anisotropy of the quark momentum distribution, and also to the quark abundance, which is expected to be underpopulated relative to thermal equilibrium. We take into ac… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…Looking forward, it will be interesting to consider pre-equilibrium dynamics in the current framework and study this effect on the dilepton and photon spectra. Indeed, it has been recently shown that intermediate mass dileptons can act as pre-equilibrium probes in heavy ion collisions [43]. We leave this for future study.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Looking forward, it will be interesting to consider pre-equilibrium dynamics in the current framework and study this effect on the dilepton and photon spectra. Indeed, it has been recently shown that intermediate mass dileptons can act as pre-equilibrium probes in heavy ion collisions [43]. We leave this for future study.…”
Section: Discussionmentioning
confidence: 88%
“…This indicates that hydrodynamic solutions exhibit a certain degree of universality resulting from rapid memory loss of initial conditions. This feature of hydrodynamic attractor has been used in recent works to establish a macroscopic description of the out-of-equilibrium dynamics of high energy heavy-ion collisions [42,43]. Recently, for a system with one dimensional longitudinal boost-invariant expansion [44], the solutions, including the attractor solution, of causal hydrodynamic evolution equations were analytically obtained for several physically relevant cases [20,38].…”
Section: Introductionmentioning
confidence: 99%
“…The main issue is clearly that experimentally only the final values of the flow harmonics, and to a lesser extent the spatial eccentricities, are directly accessible. In collisions of heavy nuclei, one may hope that accessing some characteristics of the early-time dynamics of the bulk could become possible by studying particles that decouple early from the system, in particular photons or dileptons pairs in an appropriate invariant-mass interval [46]. This may be more feasible in "small systems", although one should remember that the characteristic time scale of the evolution also becomes smaller in such systems.…”
Section: Discussionmentioning
confidence: 99%
“…They propagate through the dense gluonic system, which has an effect on their energy loss [8]. Electromagnetic observables provide another experimental window into the earliest stage of heavy-ion collisions [9,10], and originate from quarks which are the only carriers of electric charge in the medium. In order to develop a microscopic description of such observables, one must understand the interactions of quarks with a system of overoccupied gluon fields.…”
Section: Introductionmentioning
confidence: 99%